Cairo collages : Everyday life practices after the event - Abaza, Mona (Book collections on Project MUSE., 2020)
With the military seizing overt power in Egypt, Cairo's grand and dramatic urban reshaping during and after 2011 is reflected upon under the lens of a smaller story narrating everyday interactions of a middle-class building in the neighbourhood of Doqi.